Implementasi Media Pembelajaran dengan Konsep AfL Berbasis Articulate Storyline luntuk Meningkatkan Kemampuan Kognitif dan Kemandirian Siswa SMA - Romadon, Muhammad Taufik; Pujayanto, Pujayanto; Ekawati, Elvin Yusliana (Universitas Sebelas Maret, 2023)
Implementation of learning media supported by application Articulate Storyline 3 with the concept of AfL has the objective to: (1) Evaluate the learning process of class XI MIPA 4 High School Kebakraamat, (2) Describe the implementation of the learning media to improve the cognitive ability of students on the material Temperature and Calor, (3) Describes the application of learning medium to improve student independence on the materials Temperature & Calor. The research design used is class action research (PTK) with the help of Kemmis and Mc. Taggart models implemented in two cycles of action with data collection techniques including interviews, tests, observations, and document studies. The data analysis technique used is qualitative data analysis supported by quantitative data.The data validity test technique uses instrument validity and triangulation techniques. The results of the study showed that the implementation of the Articulate Storyline 3 supported learning media with the AfL concept can improve the quality of learning processes, cognitive abilities and independence of students of Class XI MIPA 4 N High School on material temperature and Calor. (1) The improvement in the evaluation of the learning process has increased from three aspects that have been met in cycle I and in the cycle II all aspects of the conformity of the RPP with the implementation have been achieved. (2) The enhancement in the presentation of the cognitive skills of students has occurred in each cycle, with the presentation in the second cycle of 86.1%. (3) The presentation of student independence has also improved from four indicators attained in the first and second cycles all indicators of independence have been reached..